Cecum intubation rate as quality indicator in clinical versus screening colonoscopy - Hoff, Geir; Holme, Øyvind; Bretthauer, Michael; Sandvei, Per; Darre-Næss, Ole; Stallemo, Asbjørn; Wiig, Håvard; Høie, Ole; Noraberg, Geir; Moritz, Volker; de Lange, Thomas (Endoscopy International Open, 2017)
Background and study aims Some guidelines recommend a minimum standard of 90 % cecal intubation rate (CIR) in routine clinics and 95 % in screening colonoscopy, while others have not made this distinction – both with limited evidence to support either view. This study questions the rationale for making such differentiation.Patients and methods We assessed cecum intubation rates amongst colonoscopies recorded in the Norwegian national quality register Gastronet by 35 endoscopists performing both clinical and screening colonoscopies. Colonoscopies were categorized into primary screening colonoscopy, work-up colonoscopy of screen-positives and clinical colonoscopy or surveillance. Cases with insufficient bowel preparation or mechanical obstruction were excluded. Endoscopists were categorized into “junior” and “senior” endoscopists depending on training and experience. Univariable and multivariable logistic regression analyses were applied.Results During a 2-year period, 10,267 colonoscopies were included (primary screening colonoscopy: 746; work-up colonoscopy of screen-positives: 2,604; clinical colonoscopy or surveillance: 6917). The crude CIR in clinical routine colonoscopy, primary screening colonoscopy and work-up colonoscopy was 97.1 %, 97.1 % and 98.6 %, respectively. In a multiple logistic regression analysis, there were no differences in CIR between the 3 groups. Poor bowel cleansing and female sex were independent predictors for intubation failure.Conclusion Cecal intubation rate in clinical colonoscopies and colonoscopy screening are similar. There is no reason to differentiate between screening and clinical colonoscopy with regard to CIR.